Brain region and gene dosage-differential transcriptomic changes in Shank2-mutant mice - Yoo, Ye-Eun; Yoo, Taesun; Kang, Hyojin; Kim, Eunjoon (Frontiers in Molecular Neuroscience, 2022)
Shank2 is an abundant excitatory postsynaptic scaffolding protein that has been implicated in various neurodevelopmental and psychiatric disorders, including autism spectrum disorder (ASD), intellectual disability, attention-deficit/hyperactivity disorder, and schizophrenia. Shank2-mutant mice show ASD-like behavioral deficits and altered synaptic and neuronal functions, but little is known about how different brain regions and gene dosages affect the transcriptomic phenotypes of these mice. Here, we performed RNA-Seq-based transcriptomic analyses of the prefrontal cortex, hippocampus, and striatum in adult Shank2 heterozygous- and homozygous-mutant mice lacking exons 6–7. The prefrontal cortical, hippocampal, and striatal regions showed distinct transcriptomic patterns associated with synapse, ribosome, mitochondria, spliceosome, and extracellular matrix. The three brain regions were also distinct in the expression of ASD-related and ASD-risk genes. These differential patterns were stronger in the prefrontal cortex where the heterozygous transcriptome displayed increased synaptic gene expression and reverse-ASD patterns whereas the homozygous transcriptome showed decreased synaptic gene expression and ASD-like patterns. These results suggest brain region- and gene dosage-differential transcriptomic changes in Shank2-mutant mice.